Using video game-based instruction in an EFL program: understanding the power of video games in education - Galvis Guerrero, Héctor Alejandro (Colombian Applied Linguistics Journal, 2011)
This small-scale action-research study examines the perceptions of four students in a military academy in Colombia undergoing the process of using a mainstream video game in their EFL classes instead of classic forms of instruction. The video game used served to approach EFL by means of language exploratory activities designed according to the context present in the video game and the course linguistic objectives. This study was conducted on the grounds that computer technology offers the possibility of enhancing EFL instruction by means of simulating and augmenting the target language context. The researcher’s belief is that video games offer a learning environment closely related to students’ experiences and preferences. Results from this study suggest that students were more entertained and attentive and demonstrated more engagement and disposition towards their English classes. Students also learned about matters related to the target language and culture, and were not only circumscribed to linguistic ones. Similarly, results from this study shed some light on the importance of offering access to technology to students before they advance to higher education that support video-gaming practices in the classroom.